2005
DOI: 10.1021/ja053686+
|View full text |Cite
|
Sign up to set email alerts
|

Geometry, Phase Stability, and Electronic Properties of Isolated Selenium Chains Incorporated in a Nanoporous Matrix

Abstract: We report the fabrication process of isolated one-dimensional Se chains incorporated in the matrix of AlPO4-5 single crystals and the experimental investigation of the geometry, phase stability, electronic properties, and electron-phonon coupling effect of these Se chains. The structure of the helical Se chains inside the channels is discussed on the basis of X-ray scattering measurements. Thermal analysis and temperature-dependent micro-Raman measurements show that Se single chains are flexible and can conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 30 publications
0
34
1
Order By: Relevance
“…Thereby, they may also end up in stabler helical structures. The fact that the Se chains are so soft can also explain why the experimental value of the dihedral angle for Se helices inside the channels of the nanoporous host, as reported by Li et al [48], differs significantly from our optimized value.…”
Section: Se Chainscontrasting
confidence: 55%
See 1 more Smart Citation
“…Thereby, they may also end up in stabler helical structures. The fact that the Se chains are so soft can also explain why the experimental value of the dihedral angle for Se helices inside the channels of the nanoporous host, as reported by Li et al [48], differs significantly from our optimized value.…”
Section: Se Chainscontrasting
confidence: 55%
“…In a recent study, Li et al [48] reported the synthesis of isolated selenium chains inside the channels of a nanoporous host. According to their study, the chains are helical with bond lengths of 4.50 a.u.…”
Section: Se Chainsmentioning
confidence: 99%
“…The inner diameter of the channel is 7.3 Å, and the separation distance between two neighboring channels is 13.7 Å. As shown in figure 1(a), selenium species are incorporated into the AlPO 4 -5 crystal channels by the vapor phase diffusion method as described previously [7]- [9]. Previous extended x-ray absorption fine structure (EXAFS) and photoacoustic spectroscopy (PAS) studies on the Se-Se distances have confirmed that single chains of Se are indeed being confined in the assembling zeolite template [10,11], mordenite with a channel diameter of 6.7 Å.…”
Section: Experiments and Calculation Methodsmentioning
confidence: 99%
“…The Se chains formed inside AFI with a diameter of 7.3 Å are studied by x-ray scattering, which determines the diameter of the chain to be 3.4 Å. If we consider that the van der Waals radius of the chain is 1.9 Å, only the formation of single chains is possible inside the channel of AFI [9].…”
Section: Experiments and Calculation Methodsmentioning
confidence: 99%
“…However, in some studies, powderlike zeolites have been employed, which may exhibit substantial surface effects. 18,28,34 In addition, there is a variety of zeolites with pore shapes and covalencies, 5 while most of previous studies have employed zeolites containing ionic pores, [15][16][17][18][19][20][21][22][23][24][25][26][27][29][30][31][32][33][34] which may mask covalent properties of chalcogens. Accordingly, further work relating atomic structures with macroscopic properties in chalcogen-loaded covalent zeolites seems intriguing.…”
Section: Introductionmentioning
confidence: 99%